ANTIBACTERIAL EFFECT OF THE INDIAN SQUID, LOLIGO DUVAUCELI (d'Orbigny), INK - Nirmale, Vivek; Nayak, B. B.; Kannappan, S.; Basu, S. (Journal of Indian Fisheries Association, 2015)
The ink of the Indian squid Loligo duvauceli (d'Orbigny) was tested forantibacterial activity. The antibacterial effect of bacteria present in the inkgland was also tested. Only one type of bacteria was found to be present inthe ink gland of squid and was identified as Photobacterium leiognathi. Amongthe various forms of ink extracts, the precipitated and freeze-dried ink showedmore pronounced antibacterial effect against Gram-negative bacteria,Salmonella, spp. Escherichia coli, Vibrio cholerae, V. parahaemolyticus andPseudomonas spp., and a less pronounced effect against Gram-positivebacteria, Staphylococcus spp. and Micrococcus spp. P. leiognathi did not inhibitany of the above bacteria. The antibacterial activity was associated with thecompounds of the ink.Keywords :Antibacterial activity, ink, Indian squid